Academic evaluation of surgical resident programs through the MEDUCPG14 program - Flores Noriega, Mónica L. (2021)
Objectives: To determine the validity and reliability of results obtained using the MEDUCPG14 instrument as well as to describe the results of the academic evaluation of surgical resident programs of a private university. Methods: A cross- sectional study was performed; the instrument was applied to 77 residents of surgical programs of Universidad Peruana Cayetano Heredia and to 41 professors. Results: A reliability coefficient of 0.959 was obtained. Two domains were found: teaching, feedback and evaluation (11 items) attained a coefficient of 0.957 and respectful treatment (3 items) attained a coefficient of 0.923. Answer rate was higher than 90%. No difference by age, gender and subspecialty was found. Conclusion: MEDUCPG-14 has adequate validity and reliability to evaluate academic performance in surgical resident programs. Four or more evaluations per professor are needed; no difference by age, sex and subspecialty was found.